Antioxidant activity Tropaeolum tuberosum Ruiz & Pavón (mashua) and its application as colorant for yogurt - Inostroza, Luis A. (2015)
The objective of the study was to evaluate the antioxidant activity and use of ethanol extract of Tropaeolum tuberosum Ruiz & Pavón (mashua) as colorant for yogurt. The antioxidant activity was evaluated using DPPH and ABTS methods. The total content of anthocyanins (TA) and polyphenols (TP) was determined by the method of differential pH and Folin-Ciocalteu, respectively. Parameters of CIEL*a*b* system were used to measure the purple color and concentration of pigment used to color natural yogurt "3500", comparing with yogurt commercial blackberry "6224" which was taken as a reference. Both yogurt samples were stored under refrigeration (4°C ± 1) for 28 days and color and pH were measured every 4 days. For sensory analysis the acceptance test was applied (p<0,05). The contents of TA and TP in the extracts analyzed were 192,63 ± 1,28 mg of cyanidin-3-glucoside/100g fresh weight (FW) and 314,12 ± 1,23 mg of gallic acid/100 g FW, respectively. The antioxidant capacity trolox equivalent obtained was 15,8 ± 0,2 µmol/g FW, using the DPPH assay, and 17,0 ± 0,2 µmol/g FW with ABTS, the extract was added to plain yogurt (1,2 mg/ 100 g) imparting the purple similar to commercial yogurt blackberry color with minimal changes that were not visually apparent; yogurt "3500" was significantly preferred by judges against the yogurt "6224". It is concluded that the extracted pigments tuber Tropaeolum tuberosum Ruiz & Pavon, possess antioxidant activity, appearing as an alternative of colorant aplicable intermediate acidity foods like yogurt.